Strategi Pengembangan UKM di Wilayah Kantor Koperasi Usaha Kecil dan Menengah Kota Bandung - Putri Purwanti, Maharani; Sudrartono, Tiris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the development strategies of Small and Medium Enterprises (SMEs) in the region of the Small and Medium Enterprise Cooperative Office in Bandung City. SMEs play a crucial role in the economy by making a significant contribution to economic growth, job creation, and innovation. Factors such as increased demand, government support, innovation, access to capital, heightened awareness, and business collaborations play a key role in the positive growth of SMEs.In this study, a case study method is employed to analyze various strategies that have been implemented in the development of SMEs in the cooperative office's region. The observations reveal that the cooperative office's role is not merely administrative but also that of a catalyst in forming an ecosystem that supports SMEs. Government support and collaboration among small business actors have proven essential in enhancing the competitiveness and capacity of SMEs.Recommendations drawn from this research include the expansion of advisory services, training, and the strengthening of collaborative networks among SMEs. The implementation of policies supporting SME sector growth is also deemed crucial, including regulatory simplification, facilitation of market access, and the development of infrastructure supporting business activities. This research provides insights into the importance of SME development strategies in the Bandung cooperative office's region and lays the foundation for holistic planning that supports the sustainable growth of SMEs and their contribution to the local economy